Snap‐through instability in mechanical metamaterials - Sen Yan; Lingling Wu; Yongzheng Wen; Jingbo Sun; Ji Zhou (Responsive Materials)
Abstract Snap‐through instability, a rapid transition between equilibrium states, has emerged as a crucial mechanism for designing mechanical metamaterials with novel functionalities, including fast motion, energy modulation, and bistable deformation. Metamaterials with snap‐through instability, known as snapping metamaterials, have enabled diverse applications, such as robotics, sensing, energy absorption, shape reconfiguration, and mechanical intelligence. Given the importance of these advancements, a comprehensive review of this field is highly desired. This paper provides an overview of recent research on snapping metamaterials, focusing on their design strategies and applications. Here, we summarized snapping metamaterials in several respects, including beam‐based structures, shell‐based structures, and origami/kirigami designs, according to their basic elements, alongside a brief discussion of their unique deformation mechanisms. Furthermore, the potential applications of snapping metamaterials are presented in terms of motion, energy, and deformation. To conclude, perspectives on the challenges and opportunities in this emerging field are highlighted, offering insights into the future research and development of snapping metamaterials.